ADAPTASI CERITA RAKYAT JAYAPRANA DAN LAYONSARI DALAM BENTUK ANIMASI 2D - Putu Ayu Riyanta Lestari; I Ketut Setiawan (Jurnal Nawala Visual, 2019)
Character education is given by the parents to their children through folktales. However, day by day folktales become more and more disappear among the influence of the even greater globalization. Thus, a synergy between folktales and technology is needed then both can be run hand in hand. The Jayaprana and Layonsari folktale’s adaptation into 2D animation movie is one kind of synergy between folktales and technology, where both can work together and support each other. In this 2D animation movie form, the story of Jayaprana and Layonsari are popularly known because it has larger publication space such as youtube, social media and smartphone. This has effect where the folktales will always be remembered even though the globalization and technology have bigger influence.